Effect of HCl Concentration on Inhibition Efficiency of A New Schiff Base on Aluminum Corrosion - DADGARINEZHAD, A.; BAGHAEI RAVARI, F.; SHEIKHSHOAIE, I. (Asian Journal of Chemistry, 2010)
In this work the corrosion inhibition of aluminum in different concentration of hydrochloric acid by using a synthesized salicylaldiminato Schiff base bis-(2-hydroxy-3-methoxy)-1,6-diaminohexane salicylaldimine are studied by weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements. The increase of HCl concentration resulted in increasing of the dissolution rate of aluminum in according to pourbaix diagram. The results of experiments indicated that this inhibitor acted as mixed inhibitor on aluminum corrosion, also increasing the inhibitor concentration up to 100 ppm resulted in reducing the rate of corrosion of aluminum in different concentration of HCl solution. Further increasing of the inhibitor concentration had an adverse effect on the efficiency of this inhibitor. The inhibition process was attributed to the formation of adsorbed film on the metal surface that protecting the metal against corrosive agents. The Langmuir adsorption isotherm fits well with the experimental data. Increasing the HCl concentration did not affect on the percentage of inhibition efficiency of inhibitor, however, the optimum inhibitor concentration remained 100 ppm for various HCl concentration. The microstructure of aluminum in various concentration of HCl without and with optimum concentration of inhibitor after 1h immersion are studied by SEM.